A life dedicated to Public Health: the nurse Félix Pedro Díaz Vázquez - María de los Reyes González Ramos; Yuliet Sánchez Seijo; Lireyma Seranega González; David Soler Marchán (Medisur)
The article socializes the results of the research on the life history of the empirical nurse Félix Pedro Díaz Vázquez, "Perico" and his contribution, from a very early age, to the development of health services in his locality, as well as the influence of his personality in the town. It is part of the period from 1930 to 1996; From a sociocultural perspective, it provides contributions on medical assistance to residents of the Castillo de Jagua-Perché seafaring community. Analysis of documents and interviews were carried out with people who knew about their work. It was found that Félix Pedro Díaz Vázquez performed important functions providing health care. The article provides a sociocultural vision to deal with local historical figures and processes, and contributes to the knowledge of a topic that is of general interest and for the history of nursing in Cienfuegos.